Environmental education and mathematics: a tool to mitigate anthropic actions on the environment (Revista de Estudos em Municipalidade, 2026)
Introduction: Personal habits affect the natural environment with direct consequences on the life quality of individuals and the community. Unsustainable behavior, such as dumping solid waste into the environment and the use of precarious basic sanitation systems in Brazilian cities, reveals a lack of zeal on the part of private institutions and public bodies responsible for control and inspection. Objective: to reflect on environmental education as an instrument for mitigating anthropic actions on the environment. Method: integrative literature review, with a survey of articles related to the object of study on Google Scholar, published between 2015 and 2022. Result: Environmental education provided in educational institutions favors the acquisition of environmentally sustainable awareness and behavior. Using their educational resources, these institutions promote a broader view of the relationship between man and the environment through contextualized learning, fostering attitudes that guarantee the common good and environmental well-being. When carried out outside the school walls, this education has the power to re-signify the relationship between individuals and nature, promoting sustainable exploration in the face of the connections between identity, culture and the environment. Conclusion: Environmental education must be present from the first years of school to the end of higher education, so that the adoption of sustainable practices becomes natural in everyday activities.
Keywords: Environment; Educational Institutions; Environmental and Mathematics education; Sustainability; Life Quality